Notes on a Marquesan Tiki-Headed Ke`a Tuki Popoi (Breadfruit Pounder) in the Founding Collection of the Pitt Rivers Museum - Coote, Jeremy (Waka Kuaka, 2015)
Until now a tiki-headed ke`a tuki popoi (Marquesan breadfruit pounder) in the collections of the University of Pennsylvania Museum of Archaeology and Anthropology has been thought to be the earliest attested example to have been collected, in 1874. It is shown that a tiki-headed ke`a tuki popoi in the founding collection of the University of Oxford's Pitt Rivers Museum was exhibited in London on 25 January 1870, making it the earliest attested example to have been collected. Some of the implications of this finding for the art history of such pounders are discussed.